Local Treatment with Adjuvant Therapy for Central Atypical Cartilaginous Tumors in the Long Bones: Analysis of Outcome and Complications in One Hundred and Eight Patients with a Minimum Follow-up of Two Years. (17th February 2016) - Dierselhuis, Edwin F.; Gerbers, Jasper G.; Ploegmakers, Joris J.W.; Stevens, Martin; Suurmeijer, Albert J.H.; Jutte, Paul C.
Abstract : Background: A central atypical cartilaginous tumor (ACT)—formerly known as chondrosarcoma grade 1 (CS1)—is a tumor of intermediate-type malignancy, often treated with surgery. The extent of surgery remains controversial, as some advocate resection and others favor local treatment by curettage. Because of the low prevalence of ACT/CS1, the available data are limited and generally not uniform. The purpose of this study was to present the outcome for a large cohort of patients with ACT/CS1 in the long bones who were treated with curettage and adjuvant phenolization and followed for a minimum of two years according to national guidelines. Methods: A retrospective study was designed to analyze data from 108 patients treated for central ACT/CS1 in the long bones between 2006 and 2012. All patients were treated with curettage and adjuvant phenolization, and defects were filled with polymethylmethacrylate, bone graft, or bone substitutes. The primary end point was local recurrence or residual tumor. Secondary end points included the type and rate of complications and reoperations. Results: All patients were free from local recurrence at a mean follow-up of 48.7 months (range, 24.3 to 97.5 months). Residual tumor was suspected in five patients, leading to a 95.4% disease-free survival rate. A fracture occurred in eleven patients (10.2%). Other complications were osseous penetration during the surgery (two patients), wound infection (one patient), arthrofibrosis (one patient), and skin necrosis (one patient). Tumor volume was related neither to the risk of fracture nor to the occurrence of residual tumor. Conclusions: In our experience, curettage of ACT/CS1 in the long bones with adjuvant phenolization is safe, even with large tumors of up to 100 cm 3 . Most worrisome is the risk of fracture, which occurred in 10.2% of our patients. Considering the relatively mild behavior of ACT/CS1, less aggressive treatment, by observation or by minimally invasive surgery, could be the next step that should be evaluated prospectively. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.